Proximal Hypospadias Repair Outcomes in Patients with a Specific Disorder of Sexual Development Diagnosis - Blake W. Palmer; William Reiner; Brad P. Kropp (Advances in Urology)
Boys with undermasculinized external genital and/or 46,XY disorders of sex development (DSD) often receive masculinizing genitoplasty. Such procedures are done to correct ventral curvature of the phallus, reposition a proximally located urethral meatus, and cosmetically correct the appearance of labioscrotal folds. No studies to date have assessed if patients with a specific DSD diagnosis have worse outcomes for severe proximal hypospadias procedures or whether or not these patients require more extensive surgical maneuvers than severe proximal hypospadias patients without a specific DSD diagnosis. We retrospectively reviewed consecutive proximal hypospadias repairs performed at our institution from 1998 to 2010 and compared the anatomy, surgical technique required for repair, and outcomes in patients with and without a definitive DSD diagnosis. Boys with a specific DSD diagnosis do have significantly more atypical anatomy when undergoing proximal hypospadias masculinizing genitoplasties. They are more likely to require associated gonad procedures but do not have an increased risk of complications or number of surgeries when compared to other proximal hypospadias patients without a specific DSD diagnosis. The risk of complications is consistent with reports in the literature, and the mean number of procedures in this contemporary study is fewer than in historic reports.